[Tomatoes on vines] - Richardson, Dennis; Agency for Public Information ([Place of publisher not identified] : Daily News)
Tomatoes on vines
Level 1 deterioration.
Available on the Special Collections Floor.
Keywords: Tomatoes; Photographs